The sin(90-theta) formula is given by sin(90-θ) = cosθ. As 90°=π/2, sin(90-θ) formula can be written as follows:

sin(π/2-θ) = cosθ.

On the other hand, sin(θ-90) formula is given by sin(θ-90) = -cosθ.

Let us now simplify the expression sin(90-theta).

## Simplify Sin(90-theta)

Question: Simplify the expression sin(90-θ). |

**Answer:**

To simplify the expression sin(90-θ), we will use the following formulas:

- sin(a-b) = sina cosb – cosa sinb.
- sin90 = 1.
- cos90 =0.

Let us put a=90 and b=θ in the above formula of sin(a-b). So we obtain that

sin(90-θ) = sin90 cosθ – cos90 sinθ

= 1⋅cosθ – 0⋅sinθ

= cosθ – 0

= cosθ.

So value of sin(90-θ) is equal to cosθ.

sin(90-θ) = cosθ |

**Also Read:** Find the value of sin(5π/2)

sin3x formula in terms of sinx

How to simplify cos(sin^{-1}x)

## Simplify Sin(θ-90)

**Question: **How to simplify Sin(θ-90)?

**Solution:**

Note that

Sin(θ-90) = sinθ cos90 – cosθ sin90

= sinθ × 0 – cosθ × 1

= 0 – cosθ

= – cosθ.

So the simplification of sin(θ-90) is equal to -cosθ, that is the value of sin(θ-90) = -cosθ.

sin(θ-90) = -cosθ |

**Read Also:** Simplify sin(π-x)

How to simplify sin(cos^{-1}x)

## FAQs

### Q1: sin(pi-theta) is equal to?

**Answer:** sin(pi-theta) is equal to cos theta.

### Q2: sin(theta-pi) is equal to?

**Answer:** sin(theta-pi) is equal to -cos(theta).